Respuesta :
Answer:
-11
Step-by-step explanation:
-2+(-9)
This is like saying,
-(2+9)
because you can factor out the negative.
-(2+9)
-(11)
-11
Answer:
-11
Explanation:
-2+(-9) is basically saying -2-9, so to figure this out in an easy way you can do 2+9 then make the number a negative. -2-9=-11, or 2+9=11 then switch it to a negative -11
-11
Explanation:
-2+(-9) is basically saying -2-9, so to figure this out in an easy way you can do 2+9 then make the number a negative. -2-9=-11, or 2+9=11 then switch it to a negative -11